Diagnostic accuracy of a charge-coupled device and a photostimulable phosphor plate in detection of non-cavitated proximal caries - Ana Paola Trevejo-Bocanegra; Alejandro Hidalgo; Jorge Beltrán (Universidad de Concepción., 2018)
Objective: The aim of this study was to compare the diagnostic accuracy of two direct digital radiography systems: the charge-coupled device (CCD) XIOS XG Sirona® and the photostimulable storage phosphor (PSP) VistaScan DürrDental®, in the detection of non-cavitated proximal caries lesions. Materials and methods: in this experimental and cross-sectional study 112 proximal surfaces from 27 molars and 31 premolars with or without proximal caries lesions were evaluated and randomly allocated in a study unit. Bitewing radiographs were acquired with a CCD XIOS XG and with the PSP VistaScan. A single X-ray unit was used for both systems. Radiographic images were assessed independently by two calibrated radiologists. Histological evaluation on a stereomicroscope was used as gold standard. Results: Sensitivity values were found to be 0.35 for CCD and 0.31 for PSP. Specificity values were found to be similar for both systems (0.867). Az values showed a low diagnostic accuracy for both sensors: 0.61 for CCD and 0.59 for PSP, no statistical difference was found between these two values (p=0.78). Conclusion: Both digital radiology systems have a high diagnostic accuracy to detect sound surfaces but low diagnostic accuracy to detect proximal carious lesions.